Holm Tetens on the Moral-Existential Argument for Theism: Reasonable Hope and Wishful Thinking - Gasser, Georg (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2017)
Holm Tetens develops in his book „Gott denken. Ein Versuch über rationale Theologie“ theoretical and practical arguments against a naturalistic and in favour of a theistic understanding of reality. In my paper I focus on Teten’s claim that we are rationally justified to hope for the truth of classical theism. I distinguish between rationally justified and unjustified forms of hope and argue that we are rationally justified to hope for the redemption of reality as promised by classical theism. However, this hope has a weaker basis of justification than Tetens seems to assume because serious objections to classical theism ought to be taken into consideration as well.